THE ROLE OF EDUCATIONAL PSYCHOLOGY IN SCHOOL READINESS: STAKEHOLDERS’ PERSPECTIVES ON THE TRANSITION FROM ECE TO PRIMARY SCHOOL - Talitha, Rahma; Christine, Sri Erwini; Manihuruk, Hema Alini; Winata, Efan Yudha (Jurnal Psikologi Jambi, 2025)
The transition from early childhood education to primary school is a critical developmental phase that significantly influences children’s success in formal learning environments. However, school readiness is often underestimated by parents, who may prioritize chronological age over developmental maturity. This study aims to explore the understanding and expectations of parents, early childhood education teachers, and primary school teachers regarding children's readiness for transition, and to compare perceptions among these stakeholders concerning readiness indicators and influencing factors. Employing a qualitative case study design, data were gathered through in-depth interviews with key informants. The findings show that while some children demonstrate readiness across cognitive, social-emotional, motor, language, and self-care domains, notable challenges persist both at the individual and systemic levels. Diverging perspectives were identified, particularly concerning ideal school entry age, psychological and developmental support, and the lack of communication between education levels. Educational psychology is positioned as a fundamental lens through which school readiness can be understood holistically—emphasizing not only developmental competencies but also the ecological and emotional support systems that shape successful transitions. These insights highlight the need for integrative transition strategies and cross-level collaboration to better support children's overall preparedness for primary education.